PENGEMBANGAN CHEMISTRY PUZZLE (CHEMPUZ) PADA MATERI TATA NAMA SENYAWA KIMIA DI SMA NEGERI 10 PONTIANAK - Lestari, Yuniar Dwi; Sahputra, Rachmat; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to determine the feasibility of Chemistry Puzzle (Chempuz) on the nomenclature of chemical compounds, and describe the responses of teachers and students in SMA Negeri 10 Pontianak towards the developed Chempuz. This research is a research and development (R&D) model with ADDIE. The subject of this study was Chempuz, which was tested on grade XI students and chemistry teachers at SMA Negeri 10 Pontianak. The instruments in this study were the feasibility assessment sheet, and the response questionnaire. The results of data processing showed that Chempuz obtained a percentage of 86.7% with the category very feasible in terms of material, language, graphic and media aspects. Based on the calculation results of questionnaire responses of students and teachers categorized very well with the results of 85% and 89.5% respectively. Thus, the results of the study showed that the developed Chempuz was suitable for use as a learning medium for chemical nomenclature material.Keywords: ADDIE, Chemistry Puzzle, Nomenclature of Chemical Compounds.